PROTOTYPING SORRY AS CHATTING FORMULA MISMATCHES ON WHATSAPP MESSENGER: A SOCIOPRAGMATIC PERSPECTIVE - Eka Fadilah; Okky Ria Vinola (Linguistik Indonesia, 2024)
Witnessing the plethora of sorry as one of the apologetic strategies in daily conversation has enthralled scholars in pragmatics, compelling them to redefine and refine its usage. This study aims twofold: to investigate prototypes of chat formula mismatches of sorry – which also includes maaf, maap, sori, and ngapunten (Javanese) – derived from WhatsApp chats and to unravel contextual factors underlying those mismatches seen from a sociopragmatic perspective. We collected 300 chat conversations, with 65% of them displaying formula mismatches in its use. The findings reveal emergent prototypes of chatting formula mismatches of those apologetic expressions, which include sarcasm, insecurity, assertive power, self-blame, disrespect, resentment, and humor. These prototypes are influenced by the level of familiarity and equal status between the sender and recipient. Furthermore, discourse markers such as ya, kan, deh, and other word fillers play a role in transcending conventional apologies to foster intimacy and harmony. This research provides a nuanced understanding of contextualized apology strategies and contributes to future pragmatics studies.